The impact of rural infrastructure and agricultural support services on poverty: The case of agrarian reform communities in the Philippines - Sununtar Setboonsarng (Asian Development Bank Institute (ADBI), 2008)
Rural poverty remains one of the biggest challenges in development. It is generally recognized that land reform, in combination with complementary support services and infrastructure development, is effective in reducing rural poverty; however, empirical evidence on the extent of the impacts is limited as are the pathways by which the impacts reach the beneficiaries. This study assesses the impacts of rural infrastructure and supported services provided by the Agrarian Reform Communities Project (ARCP) and financed jointly by the Government of the Philippines and the Asian Development Bank (ADB). Using data from the same 2,290 agrarian reform beneficiaries' households from two periods, 2001 and 2003, the study found that average annual income increased by 12%. Ownership of both household and production assets increased significantly. Among the project interventions, farm-to-market roads appeared to have the most significant impact on the communities. The benefits of the project interventions, however, were disproportionately captured by the wealthier households, resulting in worsened income distribution in the communities. In the transformation from labor use to more mechanized modes of production and transportation, the poor, i.e., the wage laborers, generally lose out, at least temporarily. Future interventions in rural infrastructure provisions should include measures to assist the poor to increase their capacity to capture the new employment opportunities generated by development interventions.
Keywords: I32; Q15; R41; 330; Ländliche Armut; Ländliche Infrastruktur; Agrarreform; Philippinen